Exclusion, Engagement, and Empathy: Revisiting Public Discourse from a Communication Perspective. (2nd January 2022) - Hansen, Solveig Lena; Hilbrich, Iris
ABSTRACT: The idea for this special issue arose from years of multidisciplinary exchange on participation and communication in technology and medicine. Which epistemological, normative, and empirical questions do arise, when endeavors of public participation deal with rejection, skepticism, and critique? This question guides our multidisciplinary perspectives. The empirical examples and theoretical accounts point out that moral justification and social effects of deliberative techniques are as controversial as the question of how to deal with moral dissent. Comprised of five interdisciplinary accounts and followed by two comments, this collection offers a complex picture of deliberative processes. These accounts show that discourses at the intersection of academia, policy, and public institutions tend to render skeptical positions as irrational, personal, or uninformed attitudes, countering them with different techniques. These techniques, so our underlying hypothesis, can be clustered into three types: exclusion, engagement, and empathy. Consequently, the papers ask which prerequisites are needed to engage in deliberations about science and technology; they analyze what happens when engagement fails due to social exclusion or misrecognition; and they scrutinize the epistemic and moral functions of empathy in deliberative engagement. The two comments summarize these papers from a viewpoint of trust and epistemic injustice.